Circular Economy: From Economic Concept to Legal Means for Sustainable Development - Oliveira,Heloísa (2020)
The purpose of this article is to provide an overview of the concept of circular economy and how it has been incorporated in public policies so far, and to determine which fundamental changes must occur in different areas of the law in order to make this transition. There has been a growing interest in this topic. Circular economy is an economic system with a zero-waste purpose in which products maintain their functionality through long life cycles, and their components maintain their value and are reincorporated into the economy in subsequent production processes. It represents a revolution from our current linear economy paradigm, and it can only be created by design. The roles of all responsible market players producers, public buyers, and private consumers must also be considered. The European Union and eight of its Member States already have strategies for a circular economy. However, only specific projects and legislation can determine a swift transition.